In vitro kinetics characterisation of polymeric nanoparticles for anticancer therapy - Azhan, Umar; Mohamed Suffian, Izzat Fahimuddin; Che Othman, Siti Fairuz; Ab. Hadi, Hazrina (IIUM Press, 2024)
World Health Organization (WHO) predicts that cancer incidence will increase in the future, thus research involving anticancer agents such as nanoparticles has gained significant importance. Nanoparticles can be made from various materials, but the focus on polymeric chitosan and/or carrageenan-based nanoparticles is significant. Research on these materials investigates dynamic parameters of in vitro drug release, stability under working conditions and stability under storage conditions (in vitro kinetics characterisations). Here, a literature review is conducted to provide in-depth insights on research methodology trends, drawbacks, suitability, suggestions for improvements and findings related to polymeric carrageenan and/or chitosan nanoparticles for anticancer therapy. Journal articles involving nanoparticles made from chitosan and/or carrageenan containing anticancer agents published between 2017 and 2022 were acquired through Google Scholar search using relevant keywords. Generally, the methods used to investigate drug release kinetics of nanoparticles can be categorised into dialysis membrane, sample and separate or direct measurement methods. Studies on the response of physiochemical characteristics towards changes in environment do not vary highly and are generalisable. Stability studies primarily measure the physicochemical changes of nanoparticles as a response measurement towards storage conditions. Both drug release selectivity and physicochemical characteristics response in different pH environments were found to be predictable via the ionisation of polymers and drugs used in different pH. The size of the nanoparticles formed during polyelectrolyte complexation process was found to be at its minimum at a balanced pH, possibly due to increased polymer-polymer attraction. The methods used for in vitro kinetics studies were generalised, and suggestions to address potential sources of errors were given in the current review. The selectivity of drug release and changes in physicochemical characteristics of the nanoparticles in different pH environments were found to largely coincide with the principles of ionisation of nanoparticle constituent.